Preparing a Compound of New Nanoparticles of Lactam, PE to Improve Their Specifications (Baghdad Science Journal, 2024)
This research deals with the properties of polyethylene (PE) using lactams with metallic nano-oxide compounds extracted from (clove) plants, specifically the flower buds of the clove tree as stabilizers and reducing agents, where the nano-oxide stabilizes and covers the natural polymer. The study aims to show that the nano-oxide performs the best bonding of the prepared composites, due to the increased surface area, and thus can bind to the prepared polymer and ability of electronic stability is due to a large number of bonds, which allow the electronic charge to be distributed and then dispersed outside the surface of the polymer, which improves the properties of the polymer and makes it an environmentally friendly material with the easiest casting technique. So that it does not harm human health and other living organisms. In this study zinc oxide nanoparticles were prepared from natural plant sources high product to be used as a catalyst for the preparation of industrially important monomers, and a lactam polymer was added in the presence of zinc oxide extracted from plant (cloves). Poly lactam is a synthetic polymer that degrades when consumed by humans. Oxide nanoparticles, monomers, and polymers were characterized using spectroscopy methods. FTIR and TGA analysis indicated that using X-ray diffraction (XRD), scanning electron microscopy (SEM) and atomic force microscopy the resulting polymer is a high molecular weight homogeneous material grafted with high-quality nanoscales.